Labor share decline across US manufacturing sub-sectors: 1979-2019 - Swayamsiddha Sarangi (The University of Utah, Department of Economics, 2023)
This paper studies the sub-sectoral contributions to aggregate manufacturing labor share decline in the US between 1979 and 2019. Using the Log Mean Divisia index (LMDI) decomposition, the decline in the manufacturing sector's labor share is decomposed into contributions from real wage growth, labor productivity growth, changes in employment shares, and relative prices arising from the constituent subsectors across three business cycles. The primary findings of the paper suggest that the downward decoupling of real wages from labor productivity is the primary contributor to the labor share decline in manufacturing. Moreover, low labor share sub-sectors (especially Chemical products, Food and Beverage and Tobacco products, and Petroleum and Coal products) have experienced an increase in their employment shares, contributing negatively to aggregate manufacturing labor share. Despite some similarities between manufacturing sub-sectors, this paper emphasizes the heterogeneity across sub-sectors to understand the possible mechanisms behind the decline of labor share.
Keywords: J30; J31; E24; L6; 330; labor share; manufacturing; subsectors; Divisia decomposition